Myocardial Infarction and Stroke Risk in Young Healthy Men Treated with Injectable Testosterone - Robert S. Tan; Kelly R. Cook; William G. Reilly (International Journal of Endocrinology)
This study was conducted to examine the association between testosterone therapy and new myocardial infarction (MI) and stroke events in a series of patients treated at Low T Centers across the United States, consisting of mainly young (mean age = 46), otherwise, healthy men. Electronic medical records were queried between the years 2009 and 2014 to identify patients diagnosed with hypogonadism, MI, and stroke, as indicated by ICD-9 codes. The incidence of MI and stroke events was compared to community-based registries. 39,936 patients recruited from 40 Low T Centers across the United States were treated and 19,968 met eligibility criteria for receiving testosterone treatment. The incidence rate ratio (IRR) for MI in testosterone- (T-) treated versus nontreated patients was 0.14 (C.I. = 0.08 to 0.18, P<0.0001) whereas the IRR for stroke for T-treated versus nontreated patients was 0.11 (C.I. = 0.02 to 0.13, P<0.0001). There was no evidence of worsening preexisting MI or stroke in patients treated with testosterone. The experience in Low T Centers shows that, in an injectable testosterone patient registry, testosterone is generally safe for younger men who do not have significant risk factors. Of patients that developed MI with testosterone, there was no association with testosterone or hematocrit levels.